No-till and direct seeding agriculture in irrigated bean: Effect of incorporating crop residues on soil water availability and retention, and yield - Souza, Joao V. R. S. [UNESP]; Saad, Joao C. C. [UNESP]; Sanchez-Roman, Rodrigo M. [UNESP]; Rodriguez-Sinobas, Leonor (Elsevier B.V., 2016)
Brazil is one of the top world producers of the staple commodity common bean (Phaseolus vulgaris L). Irregular distribution of rainfall and the lack of rain during the crop reproductive phases affect its yield and increase the demand of water for irrigation. However, in recent years, water resources have decreased and water saving has become an issue. Thus, soil management techniques, which reduce evaporation, and efficient irrigation programming, through the monitoring of soil water content, could be adopted in water scarcity scenarios. This study assesses the effect of crop residues management (incorporated IR or left on soil surface NR) in soil water availability (and its retention in the soil pore space), and yield in common beans cultivated under no-till and directly seeded in an irrigated farm located southwest of Sao Paulo state. Soil water content was monitored with TDR probes installed within the 0-20 cm layer and its retention was assessed through the soil water retention curve. For the same irrigation management, the IR led to soil water content was lower than NR but both soil managements had similar available water and their demand of water for irrigation was similar. For the same soil water content, NR soils could hold it tightly in the pore space and the root plant system would require higher energy to absorb it. Then, it is foreseen that the root system in IR soils will be shallower than in NR soils, since it will withdraw water easily within the first 20 cm, however, in NR, the roots will extend deeper searching for available water. Considering 40 kPa as a threshold value, the plants suffered water stress during all crop cycle at the same physiologic stages in both soils. The variables studied to assess yield presented no-statistical significance in the T test at significance level of 0.05. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: TDR; Crop residues; Common bean; Soil moisture; Water retention; Yield